Comparative Modeling of Harmonic Wave Reduction on Periodic Signals Through Fourier Series Integration and Passive Filter Effectiveness - Siregar, Muhammad Fadlan; Ramdan, Dadan (Faculty of Science and Technology Universitas Islam Negeri Ar-Raniry, 2026)
Abstract: Harmonic distortion is a crucial problem in electric power systems caused by the use of non-linear loads, this study presents a comparative modeling of harmonic wave reduction on periodic signals through Fourier Series integration and the use of passive filters, research methodology involves collecting real data in the field using a power quality analyzer FLUKE 435 series II on a distribution panel to identify the critical load profile. Load characteristics are analyzed through individual current decomposition (IHDi) from the 3rd to 23rd order. The observation results show that load has the highest fundamental current peak of 0.541 A with dominant distortion in the 3rd and 5th orders. The implementation of a specifically tuned RLC passive filter is proven to be effective in improving the current waveform to a pure sinusoidal in the time domain with a fundamental frequency of 50 Hz. Overall, the integration of this mathematical model is able to suppress harmonics to meet the international standard IEEE 519, ensuring the efficiency and stability of the electric power distribution system, The results of the data analysis and modeling conducted indicate that Fourier series integration is highly effective in representing the characteristics of nonlinear loads in electric power systems, determining filter values ​​that will reduce harmonics and the appropriate filter models. Abstrak: Distorsi harmonik merupakan masalah penting pada sistem tenaga listrik yang disebabkan oleh penggunaan beban non-linier. Studi ini menyajikan pemodelan komparatif pengurangan gelombang harmonik pada sinyal periodik melalui integrasi deret Fourier dan penggunaan filter pasif, metodologi penelitian melibatkan pengumpulan data dunia nyata di lapangan menggunakan power quality analyzer FLUKE 435 series II pada panel distribusi untuk mengidentifikasi profil beban kritis, karakteristik beban dianalisis melalui dekomposisi arus individual (IHDi) dari orde ke-3 hingga ke-23. Observasi menunjukkan bahwa Beban memiliki arus puncak fundamental tertinggi sebesar 0,541 A, dengan distorsi dominan pada orde ke-3 dan ke-5. Implementasi filter pasif RLC yang disetel secara khusus terbukti efektif dalam meningkatkan bentuk gelombang arus menjadi sinusoidal murni dalam domain waktu dengan frekuensi fundamental 50 Hz. Secara keseluruhan, integrasi model matematika ini mampu menekan harmonik untuk memenuhi standar internasional IEEE 519, memastikan efisiensi dan stabilitas sistem distribusi daya listrik. Hasil analisis data dan pemodelan yang dilakukan dapat disimpulkan bahwa integrasi deret fourier sangat efektif dalam merepresentasikan karakteristik beban non-linier dalam sistem daya listrik untuk menentukan nilai filter yang akan mengurangi harmonik dan model filter yang dapat digunakan.